Wheat-free for the wrong reasons? College students' attitudes and information sources pertaining to the gluten-free diet - Walker, Anne, author; Abrams, Katherine, advisor; Kodrich, Kris, committee member; Wdowik, Melissa, committee member (Colorado State University. Libraries, 2016)
The gluten-free diet has grown popular over the past years, with more people on the diet than simply celiac patients. Health professionals were concerned by the high number of people on the diet for reasons other than celiac disease because of dietary deficiencies that stem from eating gluten-free. Health scholars believed that misleading media messages touting the weight-loss and general health benefits of the diet were leading to the popularity of the gluten-free diet. However, these statements were not supported by research. In the pursuit of knowledge, research questions were developed for attitudes and information sources of the diet. Agenda setting and framing theory were used to examine survey results to better understand the possible influence media sources are having on attitudes towards the diet. To achieve a better understanding of attitudes and sources of information about the gluten-free diet, an online survey was given to 351 college students assessing their attitudes and both interpersonal and media information sources. College students were chosen as the study population based on their proclivity for fad dieting, changes in eating habits, and issues with weight. Results indicated that while students neither believed the diet was healthy nor unhealthy for everyone, they did hold negative attitudes about gluten-free as a fad diet, and believed others thought the diet was annoying and healthy. Search engine results were the most popular source of gluten-free diet information, and health type media sources were the most preferred type of media. Friends and family were the most used sources of interpersonal information, and health care providers were the least used interpersonal source of information. Students who had celiac disease or a gluten sensitivity were more likely to find gluten-free information on a search engine, on followed blogs or websites, and in magazine articles; these students were also more likely to discuss the diet with friends, family, and a health care provider. Implications and recommendations for future research were also discussed.